Influence of Balloon Size on Aortic Regurgitation in Neonates Undergoing Balloon Aortic Valvuloplasty—A Retrospective Study Over an 11‐Year Period. (13th February 2013) - HAMIDI‐MANESH, LAILA; TIBBY, SHANE M.; HERMAN, ROSIE; ROSENTHAL, ERIC; QURESHI, SHAKEEL A.; KRASEMANN, THOMAS
Abstract Background Transcatheter balloon aortic valvuloplasty has become the first‐line treatment for critical or severe aortic stenosis in neonates in many centers. Aortic regurgitation following balloon aortic valvuloplasty remains a major concern. An optimal balloon size to aortic annulus ratio in order to minimize aortic regurgitation postprocedure, while relieving the obstruction, has not yet been identified. Methods and Results In this retrospective study, data from 29 neonates with critical or severe congenital aortic valve stenosis, who underwent balloon aortic valvuloplasty in the first 28 days of life, over an 11‐year period, was evaluated. The balloon size used, ranged from 71% to 160% of the annulus size, with an average of 89%, based on the aortic annulus size as measured on angiography. The aortic regurgitation immediately following the procedure was trivial in 8 (27.6%), mild in 13 (44.8%), moderate in 7 (24.1%), and severe in 1 (3.4%) patient. The balloon to annulus ratio had no statistically significant effect on the degree of aortic regurgitation immediately after the procedure (P‐value of 0.25), at first follow‐up within 6 weeks of the procedure (P‐value of 0.76) or at follow‐up at 1 year (P‐value of 0.52). Conclusion This study did not show any significant relationship between the balloon to annulus ratio during interventional dilatation and the degree of aortic regurgitation following the procedure. (J Interven Cardiol 2013;26:200–207)